Memanamkan Nilai Keadilan Sosial dalam Kehidupan Asrama Sang Timur Malang : Inspirasi Rerum Novarium - Genoveva Jawa; Teresia Noiman Derung (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This paper aims to instill the value of social justice inspired by the encyclical Rerum Novarum issued by Pope Leo XIII in 1891 in response to the social and economic conditions resulting from the Industrial Revolution in Europe. It offers Christian values for creating a more just and humane social order. The values outlined in the encyclical not only address the context of the Industrial Revolution but are also relevant to contemporary life. In this context, they can be applied to the life at Sang Timur Dormitory in Malang. The purpose of this article is to assist the parties at Sang Timur Dormitory in Malang and readers in understanding the values of social justice in everyday life.